2021
DOI: 10.1017/ipm.2021.18
|View full text |Cite
|
Sign up to set email alerts
|

Admission patterns in a psychiatric intensive care unit in Ireland: a longitudinal follow-up

Abstract: Objective: This study aims to describe the course of admission and clinical characteristics of admissions to a psychiatric intensive care unit (PICU) in the Phoenix Care Centre (PCC), Dublin, Ireland. Methods: This retrospective chart study was conducted at the PCC, Dublin, Ireland. The cohort included all admission episodes (n = 91 complete data) over a three-year study period between January 2014 and January 2017. Results: The mean age of admitted cases was 37.1 (s.d.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Despite this, lengths of stay range from a day to over a year 3. Some studies have shown association between diagnosis and admission length in acute psychiatric services or PICU 4 5. Although diagnosis can indicate what medical treatment is required, acute management and its duration also depend on severity, comorbidity, periodicity and other features.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, lengths of stay range from a day to over a year 3. Some studies have shown association between diagnosis and admission length in acute psychiatric services or PICU 4 5. Although diagnosis can indicate what medical treatment is required, acute management and its duration also depend on severity, comorbidity, periodicity and other features.…”
Section: Introductionmentioning
confidence: 99%